Implementasi Metode Tanya Jawab Dalam Meningkatkan Kemampuan Membedakan Antara Fakta Dan Opini Dalam Teks Iklan - yuliet, desni (Komunitas Manajemen Kompetitif, 2017)
Abstract: Ad text can be judged objectively for customers where it is clear that the purpose of advertising is to attract customers to buy the products offered. In the Indonesian language, a learner needs to be able to distinguish between facts and opinions in the advertisement, because during this time the success of learners to distinguish them is still low. Through the type of classroom action research by applying the question and answer method about advertisement and data is analyzed using qualitative method, hence obtained result that implementation of question and answer method can increase learners ability to distinguish between fact and opinion in ad text. Keywords: Implementation of Q & A methods, opinions and facts